(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
It is known that it is not possible to give a complete description of the external and internal political events that took place in Ustrushana in the early Middle Ages, because the information in the ancient written sources that serve as a basis for the research is extremely scarce. Therefore, since the political life of the studied period is a continuation of the events and incidents that occurred in antiquity, there is a need to cover the political processes of this period in detail.